IMPLEMENTASI SISTEM PAKAR DIAGNOSA PENYAKIT KULIT BERBASIS WEB DENGAN METODE FORWARD CHAINING - Ichsan; Feri Susilawati (Politeknik Aceh, 2019)
Experty system is one of field in artificial intelligenc, where such system has goal to adopt various illness or desease in computer application. By build this system, it expects computer can give a precice decision like professional that has certain knowledge. This system can be used by end user to get early information about skin illness that they suffer. It also give a fast respond how to overcome the skin disease.In this experience, we use forward chaining to get decision. The system based on web which use php as programming language anda MySQL as main database.